Assessing the impact of novel risk loci on Alzheimer’s and Parkinson’s diseases in a Chinese Han cohort - Yan, Huimin; Liu, Minglei; Gao, Yuan; Yuan, Yanpeng; Liu, Xiaojing; Wang, Yangyang; Li, Lanjun; Wang, Qingzhi; Wang, Yanlin; Shi, Changhe; Xu, Yuming; Yang, Jing (Frontiers in Neurology, 2024)
Background Overwhelming evidence points to that genetic factors contributing to the development of Alzheimer’s disease (AD) and Parkinson’s disease (PD). Genome-Wide Association Study (GWAS) has come a long way in the last decade. So far, a large number of GWAS studies have been published on neurological diseases and many other diseases, providing us with a wealth of genetic information and unique biological insights. Methods Genomic DNA was extracted from both patients’ and controls’ peripheral blood samples utilizing the Blood Genome Extraction Kit. Single nucleotide polymorphisms (SNPs) were genotyped employing the enhanced multiple ligase detection reaction (iMLDR) technology. Results A case-control study was conducted, involving 211 AD patients, 508 PD patients (including 117 with dementia), and 412 healthy individuals. Age and sex stratification analysis revealed that rs871269/TNIP1 was associated with LOAD (p = 0.035), and rs5011436/TMEM106B was associated with AD in males (p = 0.044) in the genotype model. In the allele model, rs871269/TNIP1 was found to be associated with PD in the Chinese Han population (p = 0.0035, OR 0.741, 95% CI 0.559-0.983), and rs708382/GRN was identified as a risk factor for Parkinson’s disease dementia (PDD) in the Chinese Han population (p = 0.004, odds ratio (OR) 0.354, 95% confidence interval (CI) 0.171-0.733). However, no significant associations with AD or PD were observed for the remaining four loci (rs113020870/AGRN, rs6891966/HAVCR2, rs2452170/NTN5, rs1761461/LILRB2) in terms of allele or genotype frequencies. Conclusion This study identifies rs871269/TNIP1 as a potential risk factor for both LOAD and PD, rs708382/GRN as a risk factor for PDD, and rs5011436/TMEM106B as associated with AD in males when stratified by age.